Ground penetrating radar survey for risk reduction at Imja Lake, Nepal - Somos-Valenzuela, Marcelo; McKinney, Daene C.; Byers, Alton C.; Voss, Katalyn; Moss, Jefferson; McKinney, James C. (Center for Research in Water Resources, University of Texas at Austin, 2012)
This study presents observations of the structure of the terminal moraine complex at Imja Lake. Detailed ground penetrating radar (GPR) surveys were conducted at Imja Lake. The lake and the surrounding Imja glacier have been described in the previous section. This paper should contribute to the understanding of the structure of the terminal moraine and the distribution of ice in the core of the moraine. The formation of glacier lakes in the Nepal Himalaya has been increasing since the early 1960s. Accompanying this increase in the number and size of glacier lakes is an associated number of GLOF events. The Khumbu region of Nepal (which includes the Dudh Koshi basin) is regularly mentioned as an area particularly prone to GLOF events and containing important sites for possible GLOF risk reduction projects (especially in the Imja Khola). Imja lake in the Khumbu is often mentioned as a potentially dangerous glacier lake (PDGL) and its GLOF risk has been investigated for more than 20 years (Armstrong, 2010). In May and September 2012, the authors visited the lake and observed the rapid rate of change of the terminal moraine complex. They performed ground penetrating radar surveys of most of the terminal moraine complex and mapped the ice core of the moraine. Imja Lake is currently the focus of several groups in an effort to reduce the risk of a GLOF posed by the increasing lake level. The presence or absence of ice in the core of the terminal moraine complex is of critical importance in designing a risk reduction program for the lake. This work has used Ground Penetrating Radar (GPR) to investigate the internal structure of the moraine complex in order to map out the ice thickness in critical areas. The results of the GPR survey show that there is extensive ice present in the core of the terminal moraine complex at Imja Lake (see Figure 8). The thickest areas of ice are in the moraine near the western end of the lake on the northern side of the lake outlet. The ice in this region is several tens of meters thick and ...